Randomized clinical trial of pigtail catheter versus chest tube in injured patients with uncomplicated traumatic pneumothorax. Issue 2 (23rd December 2013) - Kulvatunyou, N; Erickson, L; Vijayasekaran, A; Gries, L; Joseph, B; Friese, R F; O'Keeffe, T; Tang, A L; Wynne, J L; Rhee, P
Abstract: Background: Small pigtail catheters appear to work as well as the traditional large-bore chest tubes in patients with traumatic pneumothorax, but it is not known whether the smaller pigtail catheters are associated with less tube-site pain. This study was conducted to compare tube-site pain following pigtail catheter or chest tube insertion in patients with uncomplicated traumatic pneumothorax. Methods: This prospective randomized trial compared 14-Fr pigtail catheters and 28-Fr chest tubes in patients with traumatic pneumothorax presenting to a level I trauma centre from July 2010 to February 2012. Patients who required emergency tube placement, those who refused and those who could not respond to pain assessment were excluded. Primary outcomes were tube-site pain, as assessed by a numerical rating scale, and total pain medication use. Secondary outcomes included the success rate of pneumothorax resolution and insertion-related complications. Results: Forty patients were enrolled. Baseline characteristics of 20 patients in the pigtail catheter group were similar to those of 20 patients in the chest tube group. No patient had a flail chest or haemothorax. Pain scores related to chest wall trauma were similar in the two groups. Patients with a pigtail catheter had significantly lower mean(s.d.) tube-site pain scores than those with a chest tube, at baseline after tube insertion (3·2(0·6) versus 7·7(0·6); P < 0·001), on day 1 (1·9(0·5) versus 6·2(0·7); P < 0·001) and day 2 (2·1(1.1) versus 5·5(1·0); P = 0·040). The decreased use of pain medication associated with pigtail catheter was not significantly different. The duration of tube insertion, success rate and insertion-related complications were all similar in the two groups. Conclusion: For patients with a simple, uncomplicated traumatic pneumothorax, use of a 14-Fr pigtail catheter is associated with reduced pain at the site of insertion, with no other clinically important differences noted compared with chest tubes. Registration number: NCT01537289 (http://clinicaltrials.gov ). Abstract : No difference in pain scores